BEHAVIORISM, INNATISM, AND INTERACTIONISM IN ENGLISH TEACHING AND LEARNING - Dwi Ratnasari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2019)
Abstract:In Indonesia, English has been introduced into school curriculum since junior secondary schools at the first grade though some elementary schools have English as their local content since the fourth grade. Indonesian government has been engaged in activities for many years with the aim of improving the English competency of school graduates in the country. However, the reality has been too far from the expectation. The English skills’ output of the students is still categorized into a low proficiency level. As stated in Education First, English Proficiency Index (EPI) in Indonesia in 2018 is ranked 51 out of 88 countries in the world. Therefore, there needs to be an explanation of what makes Indonesian students’ English proficiency low and how to teach or learn English by considering language acquisition theories, namely behaviorism, innatism, and interactionism. It is the purpose of this paper to briefly explain about these issues. Keywords: behaviorism, innatism, interactionism, English, teaching, learning